2014
DOI: 10.1038/jid.2014.162
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Mobilization of Endogenous Stem Cells Significantly Promotes Skin Regeneration after Full-Thickness Excision: The Synergistic Activity of AMD3100 and Tacrolimus

Abstract: Stem cell therapy has shown promise in treating a variety of pathologies including skin wounds, but practical applications remain elusive. Here we demonstrate that endogenous stem cell mobilization produced by AMD3100 and low-dose Tacrolimus is able to reduce by 25% the time of complete healing of full-thickness wounds created by surgical excision. Equally important, healing was accompanied by reduced scar and regeneration of hair follicles. Searching for mechanisms, we found that AMD3100 combined with low-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 44 publications
7
76
1
Order By: Relevance
“…Mobilization of endogenous stem cells with AMD3100 and low-dose FK506 results in immunosuppressive-free long-term survival in maximally immunologically mismatched swine Similar to our reports in rodents (27,28), subcutaneous injection of AMD3100 (1 mg/kg) plus low-dose FK506 (0.03 mg/kg) in swine significantly increased CD34 + stem cells in peripheral blood. CD34 + stem cells reached peak levels in peripheral blood at 3 h and remained at higher levels up to 48 h after the dual-drug injection ( Figure 1A).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Mobilization of endogenous stem cells with AMD3100 and low-dose FK506 results in immunosuppressive-free long-term survival in maximally immunologically mismatched swine Similar to our reports in rodents (27,28), subcutaneous injection of AMD3100 (1 mg/kg) plus low-dose FK506 (0.03 mg/kg) in swine significantly increased CD34 + stem cells in peripheral blood. CD34 + stem cells reached peak levels in peripheral blood at 3 h and remained at higher levels up to 48 h after the dual-drug injection ( Figure 1A).…”
Section: Resultssupporting
confidence: 86%
“…In a rat kidney transplant model (29), we have shown that FK506 alone increased SDF-1 presence in the transplant. We have reported that cells with macrophage phenotypes are liberated from the bone marrow by FK506 and recruited to the injured sites (27,28 It has been reported that rejection of donor skin grafts occurred in 9-11 days in long-term specific tolerance to one haplotype class I plus minor antigen disparate renal allografts in miniature swine (33). Coincident with skin rejection, most animals developed a transient rise in creatinine to 4.9 AE 1.2 mg/dL (n = 10), with normal levels returning in all animals within 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This antagonist is already being used in the clinic to stimulate mobilization of hematopoietic stem cells from the bone marrow into the blood in cancer patients. 48 A recent study demonstrates that local injection of AMD3100 at the site of injury increases recruitment of endothelial progenitor cells to wounds in rodent models. 48 An important advantage of administering either SDF-1 or AMD3100 to the wound is that it directly targets endogenous stem cells and circumvents the challenges with isolating, expanding, and then delivering stem cells to the wound.…”
Section: Designing a Chemokine-based Therapeutic To Enhance Msc Hominmentioning
confidence: 99%
“…48 A recent study demonstrates that local injection of AMD3100 at the site of injury increases recruitment of endothelial progenitor cells to wounds in rodent models. 48 An important advantage of administering either SDF-1 or AMD3100 to the wound is that it directly targets endogenous stem cells and circumvents the challenges with isolating, expanding, and then delivering stem cells to the wound. However, if the goal is to also recruit exogenous MSC then recognized challenges associated with MSC delivery to the wound need to be overcome.…”
Section: Designing a Chemokine-based Therapeutic To Enhance Msc Hominmentioning
confidence: 99%